Migrant perinatal depression study: a prospective cohort study of perinatal depression on the Thai-Myanmar border - Fellmeth, Gracia (BMJ Open, 2018)
PURPOSE: Perinatal depression is a significant contributor to maternal morbidity. Migrant women in resource-poor settings may be at increased risk, yet little research has been conducted in low-income and middle-income settings. This prospective cohort study of migrant women on the Thai-Myanmar border aims to establish prevalence of perinatal depression, identify risk factors for perinatal depression and examine associations with infant outcomes. PARTICIPANTS: Participating women are labour migrants and refugees living on the Thai-Myanmar border. A total of 568 women were recruited in their first trimester of pregnancy and are being followed up to 1-year postpartum. FINDINGS TO DATE: At baseline, women in our study had a median age of 25 years, the predominant ethnicity was Sgaw Karen (48.9%), agriculture was the main employment sector (39.2%) and educational attainment was low with a median of 4 years of education. In the first trimester of pregnancy, a quarter (25.8%; 95% CI 22.3 to 29.5) of all women were depressed as diagnosed by the Structured Clinical Interview for the Diagnosis of DSM-IV Disorders. FUTURE PLANS: Follow-up is ongoing and expected to continue until January 2018. The prevalence of depression at later stages of pregnancy and during the first postpartum year will be identified, and associations between depression status and demographic, social, migration-related, medical, obstetric and infant factors will be quantified. TRIAL REGISTRATION NUMBER: NCT02790905.